Analysis of Marketing Strategies to Increase Shrimp Sales at PT. Indomina Langgeng Sejahtera - Dede Rianatullah (International Journal of Social Service and Research, 2022)
The research aims to determine the appropriate marketing strategy for companies to increase market share and to continue to exist amid ever-increasing business competition. This research deals with  marketing strategies, which include strengths, weaknesses, opportunities, threats and market share owned and marketing strategies developed using SWOT analysis tools (Strengths, Weakness, Opportunities, Threats).Business development is now increasing from year to year, will automatically be coupled with increasing competition from business people, such as PT. Indomina Langgeng Sejahtera which was established in 2015 with a marketing strategy offering a variety of processed shrimp products. Based on the research conducted, it turns out that PT. Indomina Langgeng Sejahtera has advantages, based on IFAS and EFAS analysis, the results of the analysis show that the strength and weakness factor (IFAS) shows 2.65, and the opportunity and threat factor (EFAS) is 2.80. Strength and opportunity factor (SO) of 3.80, strength and threat (ST) of 2.70, weakness and opportunity factor (WO) of 2.75, and for weakness and threat factor (WT) of 1.65. From the results of this analysis, it can be seen that PT. Indomina Langgeng Sejahtera has a great power to take advantage of opportunities and minimize threats. PT. Indomina Langgeng Sejahtera can also minimize weaknesses to take advantage of opportunities, moreover in minimizing weaknesses to avoid threats. Therefore PT. Indomina Langgeng Sejahtera can utilize its strengths and opportunities optimally.